MEDIASI ADAT NIA LAWO LAMBU SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA TANAH WARISAN DI DESA DETUBINGA, KABUPATEN SIKKA - Rade, Stefanus Don; Zigha Nanga, Antonia Alfiayu; Bani, Ferdinandus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study examines the mediation of Nia Lawo Lambu customs as an alternative to resolving heritage land disputes in Detubinga Village, Sikka Regency. Using empirical legal research methods, this study analyzes the implementation, values, and effectiveness of Nia Lawo Lambu in the context of Indonesian legal pluralism. The results of the study show that Nia Lawo Lambu is an effective dispute resolution mechanism, supported by the legitimacy of formal law, the role of Mosalaki as a mediator, and the active participation of the community. These practices reflect the values of hospitality, equality, simplicity, and sustainability in Lio society. Despite facing various modernization challenges, Nia Lawo Lambu remains relevant as an instrument for maintaining social harmony and sustainable conflict resolution. This research recommends strengthening the integration between customary practices and the national legal system, as well as the preservation of traditional values for future generations